Visceral leishmaniasis: Therapeutic challenges and the potential of microalgae as a source of antileishmanial compounds (Research, Society and Development, 2024)
Leishmaniases are diseases caused by protozoa of the Leishmania genus, transmitted by sandflies, manifesting as visceral, cutaneous, or mucocutaneous forms. Classified as a neglected tropical disease, it disproportionately affects vulnerable populations, especially in low-income regions. This narrative literature review aimed to assess current knowledge on the therapeutic potential of microalgal extracts and compounds for the treatment of visceral leishmaniasis. The research was conducted using the PubMed, SciELO, and Google Scholar databases, employing the keywords Leishmania infantum, Visceral Leishmaniasis, Microalgae, Cyanobacteria, Treatment, and Extracts, as well as their combinations, and considering publications from 2013 to 2024. Original studies analyzing microalgae and cyanobacteria as sources of bioactive compounds against Leishmania infantum were prioritized. Current treatments for human visceral leishmaniasis face severe limitations, including toxicity, parasite resistance, and high costs, while therapeutic options for dogs are largely ineffective. Microalgae and cyanobacteria are emerging as promising sources of bioactive compounds with antiprotozoal activity, showing efficacy comparable to certain drugs used in conventional treatments. Therefore, investigating microalgae and cyanobacteria as sources of antileishmanial compounds is crucial, given the limitations of current therapies. These organisms exhibit significant biotechnological potential but remain underexplored. Investments in bioprospecting may reveal safer, more accessible, and more effective therapeutic alternatives to address this global health challenge.